2014
DOI: 10.1002/cmdc.201400075
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Antiviral Potency and Lipophilicity of Halogenated 2,6‐Diarylpyridinamines as a Novel Class of HIV‐1 NNRTIS

Abstract: Nineteen new halogenated diarylpyridinamine (DAPA) analogues (6a-n and 8a-e) modified on the phenoxy C-ring were synthesized and evaluated for anti-HIV activity and certain drug-like properties. Ten compounds showed high anti-HIV activity (EC50 < 10 nM). Particularly, (E)-6-(2”-bromo-4”-cyanovinyl-6“-methoxy)phenoxy-N2-(4′-cyanophenyl)pyridin-2,3-diamine (8c) displayed low nanomolar antiviral potency (3–7 nM) against wild-type and resistant viral strains with E138K or K101E mutation, associated with resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
(28 reference statements)
1
11
0
Order By: Relevance
“…This comes in accordance with the previous studies reporting that iodo-derivatives exhibited the most potent activity as helicase inhibitors against replication of coronaviruses (24). In addition, it was reported that the aromatic substituent influences dramatically te anti-corona viruses activity (25). The current study reveals that orientation of halogen affected the activity, so that para--substituted compounds within the series 9-16 were showed higher helicase inhibitory activity compared to the ortho-ones.…”
Section: Structure-activity Relationship (Sar)mentioning
confidence: 57%
“…This comes in accordance with the previous studies reporting that iodo-derivatives exhibited the most potent activity as helicase inhibitors against replication of coronaviruses (24). In addition, it was reported that the aromatic substituent influences dramatically te anti-corona viruses activity (25). The current study reveals that orientation of halogen affected the activity, so that para--substituted compounds within the series 9-16 were showed higher helicase inhibitory activity compared to the ortho-ones.…”
Section: Structure-activity Relationship (Sar)mentioning
confidence: 57%
“…Preserving these known necessary pharmacophore elements, compound 34 was synthesized by modification of Y and R 2 substituents located on the phenoxy ring (A ring). This compound demonstrated excellent anti‐HIV‐1 potency against both wild‐type and resistant virus strains with mutation on E138K or K101E positions . It also showed favorable physiochemical properties and a good equilibrium between potency and lipophilicity.…”
Section: Modification Of Existing Nnrti Scaffoldsmentioning
confidence: 99%
“…Subsequently, multiple structural modifications were introduced to identify structure-activity relationship (SAR) and structure-property relationship (SPR) correlations for DAANs and DAPAs as new HIV-1 NNRTI agents. The subsequent leads 2b 13 (DAAN) and 3b 14 (DAPA) exhibited not only extremely high potency against both wild-type (EC 50 values of 0.39 and 3.25 nM, respectively) and drug-resistant (EC 50 values of 1.8–3.4 and 3.5–6.9 nM, respectively) viral replication but also improved druglike properties. Lead 2b had a desirable log P value of 3.68 and a high water solubility of 90 µg/mL at pH 2.0, but its higher metabolism and instability in various solvents prompted continued structural optimization.…”
Section: Introductionmentioning
confidence: 99%